Predictors of pregnant and breastfeeding women’s intention to use traditional Chinese medicine: a cross-sectional study from China - Zanmei Li; Jiao Li; Yushan Lan; Liangkun Ma; Lei Xuan (BMC Complementary Medicine and Therapies)
Abstract Background Traditional Chinese medicine (TCM) is widely used by pregnant and breastfeeding women in China, yet predictors of its use intention remain understudied in mainland China. This study applied an extended Theory of Planned Behavior (TPB) framework to identify factors influencing TCM use intention in this population. Methods A cross-sectional survey was conducted among 264 pregnant and breastfeeding women from diverse regions in mainland China between July and October 2023. Data were collected through an online questionnaire that included demographic information, TPB-based measures (attitudes, subjective norms, perceived behavioral control, intention), and past TCM use experiences. Structural Equation Modeling (SEM) was used to test hypothesized relationships. Results The results showed that 37.5% of participants reported using TCM during pregnancy or lactation. The extended TPB model explained 84.5% of variance in intention, with subjective norms having the strongest impact (β = 0.435; p < 0.001), followed by attitudes (β = 0.304; p < 0.001) and perceived behavioral control(β = 0.294; p < 0.001). Past experience with TCM also significantly influenced both attitudes and intentions. The model demonstrated excellent fit (χ²/df = 1.53; CFI = 0.99; RMSEA = 0.04). Conclusions This study demonstrates that TCM use during pregnancy and lactation is common in China, and that subjective norms, attitudes, perceived behavioral control, and prior experience are key predictors of intention to use TCM. These findings underscore the importance of integrating cultural and social considerations into healthcare practices. Healthcare providers should be aware of the significant role of family in decision-making and incorporate culturally sensitive counseling into maternal care. Policymakers should strengthen regulatory oversight of TCM to ensure its safe and effective use during pregnancy.